The pharmacology, pharmacokinetics, and toxicity of spinosin: A mini review - Kuang, Xiaolan; She, Ganshu; Ma, Ting; Cai, Wanna; Zhao, Jingjing; Liu, Bo; Xu, Fangfang (Frontiers in Pharmacology, 2022)
Spinosin, a natural ﬂavone-C-glycoside that mainly isolated from the seeds of Ziziphus jujuba Mill. var. spinosa. It exerts the effects to ameliorate the neurological disorders, such as hypnosis effects, improvement of cognitive function, sedation effects, and anxiolytic effects, as well as anti-melanogenic effect, cardioprotective effects, anti-cancer activity. However, the insufficient basic research, unclear mechanisms, and poor bioavailability may limit the prospects of spinosin in clinical utilization. In this review, we comprehensively summarized the latest information on the pharmacology, pharmacokinetics, toxicity and NMR characteristic of spinosin, to evaluate its potential therapeutic for clinical application, hoping to provide some rational perspective for the innovative agent development and usage of spinosin in future.